Pro-Poor Public Spending Reform : Uganda's Virtual Poverty Fund - Williamson, Tim; Canagarajah, Sudharshan (World Bank, Washington, DC, 2012)
The Poverty Action Fund (PAF) was introduced in Uganda in 1998 to reorient government expenditures towards implementing its Poverty Education Action Plan (PEAP) as well as to account for Heavily Indebted Poor Country (HIPC) resource use. This paper notes the successes of the PAR, the negative aspects, and the key lessons learned. Successes include: reorienting budget allocations towards pro-poor service delivery and demonstrating the additionality of debt relief; mobilizing donor resources and harmonizing conditions; and improved budget predictability, transparency, and accountability. The negative aspects include: unbalanced budget allocations, biased budget implementation, partial monitoring and evaluation, and no exit strategy. The key lessons were: To be effective, a Virtual Poverty Fund (VPF) should be simple and limited to the identification of Poverty Reduction Strategy Paper (PRSP) priority expenditures in the budget classification system; a VPF should be introduced in a way that supports rather than replaces the implementation of such comprehensive improvements in budget preparation and implementation; and a VPF does not bypass the need to have a PRSP and an effective budget process that identify priority pro-poor expenditures to be included in the VPF as part of a broader policy framework for growth and poverty reduction.